THE ROLE OF ANTIOXIDANT DEFENSE DISTURBANCES IN PATHOGENESIS OF THE LATE MANIFESTATIONS OF TRAUMATIC DISEASE AFTER CRANIO-SKELETAL INJURY AND EFFECTIVENESS OF ITS CORRECTION BY PHYTOMIXTURE - Servatovych, A. M.; Gudyma, A. A. (Journal of Education, Health and Sport, 2015)
Servatovych А. М., Gudyma A. A. The role of antioxidant defense disturbances in pathogenesis of the late manifestations of traumatic disease after cranio-skeletal injury and effectiveness of its correction by phytomixture. Journal of Education, Health and Sport. 2015;5(12):271-278. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35420 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A271-278 http://pbn.nauka.gov.pl/works/681512 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015. UDK :612.015.11-02:616.711/.714-001-036.8-085.322]-092.9 THE ROLE OF ANTIOXIDANT DEFENSE DISTURBANCES IN PATHOGENESIS OF THE LATE MANIFESTATIONS OF TRAUMATIC DISEASE AFTER CRANIO-SKELETAL INJURY AND EFFECTIVENESS OF ITS CORRECTION BY PHYTOMIXTURE А. М. Servatovych, A. A. Gudyma SHEI “I. Ya. Horbachevsky Ternopil State Medical University Healthcare Ministry of Ukraine” Summary In a response to cranio-skeletal injury during late manifestations of traumatic disease in the body of experimental animals is proceeded significant decrease of superoxide dismutase and catalase activity in liver tissue. An increasing of ceruloplasmin content in serum from 14 to 35 days of post-traumatic period, the content of SH-group in the liver tissue – after 21 and 28 days is observed. The application of Phytomixture that started on 14th day of experiment, in comparison with animals without correction, accompanied by greater activity in the liver tissue of antioxidant enzymes and lower content in serum of ceruloplasmin in all periods of observation and more content of SH-groups after 28 days in post-traumatic period. After 28-35 days of Phytomixture influence a normalization of blood serum ceruloplasmin appears, after 21-35 days – the normalization of catalase activity and content of SH-groups in liver tissue occurs. This indicates a strong antioxidant effect of Phytomixture in the late period after cranio-skeletal injury. Key words: cranio-skeletal injury, antioxidant defense, phytotherapy, phytomixture.